Gaya Hidup Remaja dalam Mengimitasi Budaya Pop Korea Melalui Televisi - Nurhasanah Nurhasanah; Nurul Annisah; Elsa Ramayeni; Zumri Syahferi Harahap; Sukma Erni (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
Korean pop culture, or K-Pop, has become a global phenomenon that influences many aspects of the lives of teenagers around the world. This research aims to understand how teenagers' lifestyles are influenced by Korean pop culture through television programs. Qualitative research methods were used to explore teenagers' experiences and perceptions of consuming Korean pop culture via television. Research findings show that teenagers often adopt lifestyles promoted by the K-Pop celebrities they see on television screens. They follow fashion trends, hairstyles and even diets inspired by Korean television programs. The results of this research provide deeper insight into the impact of Korean pop culture on teenagers and its implications for local cultural identity.